(untitled) (International Conference on Education, Psychology and Humanities, 2026)
The growing heterogeneity of school classrooms requires teaching methodology to move beyond uniform content delivery toward flexible and diagnostically informed instruction. This need is especially visible in biology, where students differ in prior knowledge, pace of learning, scientific vocabulary, motivation, visual-spatial reasoning, and readiness for laboratory and inquiry-based tasks. The purpose of this thesis is to substantiate methodological approaches for improving teaching in biology classes by taking into account students’ individual characteristics. The study is based on theoretical analysis and synthesis of contemporary research on differentiated instruction, personalized learning, student diversity, and biology education. The results show that effective methodology in biology depends on the integration of diagnostic assessment, differentiated content and tasks, multimodal explanation, scaffolded inquiry, formative feedback, and flexible use of digital tools. The study argues that attention to individual characteristics does not weaken common educational standards; on the contrary, it creates more equitable access to core biological concepts and scientific reasoning. The thesis concludes that improving biology teaching methodology requires a systemic didactic model in which the teacher coordinates goals, methods, resources, and assessment in relation to the learner’s educational profile.